#### Answer

a) $b=\dfrac{A}{h}$
b) $h=\dfrac{A}{b}$

#### Work Step by Step

a) Using the properties of equality, in terms of $
b
,$ the given formula, $
A=bh
,$ is equivalent to
\begin{array}{l}\require{cancel}
\dfrac{A}{h}=\dfrac{bh}{h}
\\\\
\dfrac{A}{h}=b
\\\\
b=\dfrac{A}{h}
.\end{array}
b) Using the properties of equality, in terms of $
h
,$ the given formula, $
A=bh
,$ is equivalent to
\begin{array}{l}\require{cancel}
\dfrac{A}{b}=\dfrac{bh}{b}
\\\\
\dfrac{A}{b}=h
\\\\
h=\dfrac{A}{b}
.\end{array}